Innovations in the forest products industry: the Malaysian experience - Ratnasingam, Jegatheswaran; Lim, Tau Wai; Thanasegaran, Ganesh G.; Ioras, Florin; Vacalie, Cristina; Coman, Claudiu; Lu, Weng Ming (AcademicPres, University of Agricultural Sciences and Veterinary Medicine, 2013)
The forest products industry is an important socioeconomic sector to many developing countries, both in terms of foreign exchange earnings and employment. In the case of Malaysia, the industry has been one of the fastest growing manufacturing sectors in the country, driven primarily by comparative advantages derived from factor inputs. However, with increasing competition from other cheaper producing nations particularly China and Vietnam, the Malaysian forest products industry is forced to transform and move along the value-chain through innovation and value-addition. Although the government has played a pivotal role in providing a broad policy framework to support value-adding and innovative activities, success on the ground has been limited. The creativity environment, which is plagued with by low-wage economy, coupled with limited network between research, market and industrial enterprises have stifled innovation within the industry. The lack of information and the poor quality human capital has also contributed to the limited innovation within the forest products industry in the country. Against this background, most innovation within the industry is confined to the realms of alternative raw materials, with minimal technological and design variations. Although extensive research and development activities are undertaken, the commercialization potential of the research outputs is limited due to being not market-driven. Inevitably, innovation in the forest products sector must be based on market-needs and must be driven through technological and design change in order to ensure long-term competitiveness.